Lateral hypothalamus involvement in control of stress response by bed nucleus of the stria terminalis endocannabinoid neurotransmission in male rats - Gomes-de-Souza, Lucas [UNESP]; Costa-Ferreira, Willian [UNESP]; Mendonça, Michelle M.; Xavier, Carlos H.; Crestani, Carlos C. [UNESP] (Springer Nature, 2021)
The endocannabinoid neurotransmission acting via local CB1 receptor in the bed nucleus of the stria terminalis (BNST) has been implicated in behavioral and physiological responses to emotional stress. However, the neural network related to this control is poorly understood. In this sense, the lateral hypothalamus (LH) is involved in stress responses, and BNST GABAergic neurons densely innervate this hypothalamic nucleus. However, a role of BNST projections to the LH in physiological responses to stress is unknown. Therefore, using male rats, we investigated the role of LH GABAergic neurotransmission in the regulation of cardiovascular responses to stress by CB1 receptors within the BNST. We observed that microinjection of the selective CB1 receptor antagonist AM251 into the BNST decreased the number of Fos-immunoreactive cells within the LH of rats submitted to acute restraint stress. Treatment of the BNST with AM251 also enhanced restraint-evoked tachycardia. Nevertheless, arterial pressure increase and sympathetically-mediated cutaneous vasoconstriction to restraint was not affected by CB1 receptor antagonism within the BNST. The effect of AM251 in the BNST on restraint-evoked tachycardia was abolished in animals pretreated with the selective GABAA receptor antagonist SR95531 in the LH. These results indicate that regulation of cardiovascular responses to stress by CB1 receptors in the BNST is mediated by GABAergic neurotransmission in the LH. Present data also provide evidence of the BNST endocannabinoid neurotransmission as a mechanism involved in LH neuronal activation during stressful events.